Managing conflict across cultures, values and identities: a case study in the South African automotive industry - Mayer, Claude-Hélène (Rhodes University, Faculty of Commerce, Department of Management, 2008)
Over the past fifty years, interest in the field of conflict management and peacekeeping has developed worldwide. During the same time, the potential for trans-ultural) conflict has escalated. This can mainly be attributed to the trend towards globalisation, as well as the growing complexity of societies increasingly experiencing more intercultural encounters or cultural transition situations and work-related or organisational conflicts. Cultural transition situations occur in the South African international automotive industry where the emergence of international co-operation, such as joint ventures (driven by globalisation) and new diversity management trends, have changed the way business is conducted. Due to these changes, employees of diverse origins with different cultures, values and identities work together, experiencing work-related conflicts. The purpose of this study was to assess managerial perspectives on conflict, identity and values, as well as on how (trans-cultural) conflict is managed in a selected international organisation in the South African automotive industry. The contribution of this study is twofold, namely to increase the understanding of the complexities of conflict in organisations; and to provide recommendations for conflict resolution strategies to manage (trans-cultural) conflict constructively by considering the values and identity aspects of those individuals involved. This study comprises a single explanatory case study which made use of qualitative data collection and analysis to investigate managerial perspectives on conflict, identity and values, as well as the management thereof, in the selected international organisation in the South African automotive context. Based on the main findings from this case study, it could be concluded that managers with diverse backgrounds experience work-related conflicts which are related to value and identity concepts in the selected organisation. The conflicts experienced fell into the categories of Communication and Treatment, Position and Competition, Organisation and Race and Gender.An overview of the occurrence frequency of value statements revealed that equality, communication and respect were the most commonly indicated values in conflicts. These value concepts include sub-concepts such as: · for equality: race, gender and human equality; · for communication: open, personal, free, decent, calm and proactive communication; and · for respect: mutual respect for self and others. With regard to value concepts and according to value domains of Schwartz (1994) and Schwartz and Bilsky (1987), the value dimensions of selftranscendence comprised the highest number of value statements. This dimension included the value domains of universalism and benevolence. Conflict in the data material was interlinked with identity. The extracts, based on the key words of the identity factors, demonstrated that the identity factors were related to either a weakening or strengthening effect on identities. Social and identity multiplicity in managers provides creativity spaces and flexibility in cases of strong identity patterns. Particularly with weak identities, the existence of conflict potentials could lead to complex conflicts and challenges in conflict management. Communication was most often mentioned as important to successful conflict resolution management and included examples such as round-table talks, smooth communication, face-to-face communication and room meetings. Communication was followed in frequency by strategies of internal intervention, which included the use of the formal structure of the organisation to resolve conflicts.
Keywords: Conflict management -- South Africa; Automobile industry and trade -- South Africa; Automobile industry workers -- South Africa; Communication in management -- South Africa; Intercultural communication -- South Africa; Culture conflict -- South Africa; Diversity in the workplace -- South Africa